A Validated Screening Instrument for Identifying Intimate Partner Violence in South Asian Immigrant Women - Soglin, Lenore F. (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) for South Asian immigrants is prevalent and has many unique sociodemographic and cultural factors associated with it. Current screening instruments do not address the unique cultural factors associated with IPV in this population. The South Asian Violence Screen (SAVS) is a 14-item screening tool for IPV designed based on the specific demographic and cultural issues affecting South Asian immigrant women in the United States. The tool was validated using the Index of Spouse Abuse (ISA), a well-established survey instrument for detecting IPV. The participants in the study included 116 South Asian immigrant women, who were recruited from a medical clinic and two community centers in Chicago, IL. With a prevalence of 23.3% of women reporting physical abuse and 28.4% reporting nonphysical abuse, the negative predictive value of the SAVS compared with the ISA was 0.99 and 0.97 for physical abuse and nonphysical abuse, respectively. When compared with the ISA-physical, the sensitivity and specificity were 0.96 and 0.87, respectively, and when compared with the ISA-nonphysical, the sensitivity and specificity were 0.94 and 0.92, respectively. This study demonstrates that the SAVS is an effective and efficient screening tool in the South Asian immigrant population in Chicago.